I'm A Loser, Baby: An Analysis of Party Responsiveness to Vote Loss - Harrington, Sinéad C M (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2025)
Understanding how parties change is fundamental to understanding their role in representative democracy, and the alternatives that are available to voters. In particular, understanding how they change in response to election results highlights the impact that voters can have on the political system beyond the direct effect of determining the next government. While many previous studies have sought to quantify the relationship between electoral performance and subsequent party platforms, the empirical approaches used do not accurately capture the specific electoral threats indicated by election results. Based on a theoretical approach that sees parties as conservative and risk-averse, I argue that in order to accurately measure responsiveness to election results, studies need to focus on the specific electoral threats indicated by the results in question. While previous studies have focused on measuring responses to the rise of competing party families or to overall vote loss, I refine this relationship by introducing a dataset that captures the extent of vote loss from the responding party to individual party families. In doing so, I measure responsiveness to the specific electoral threat posed by a given party family to the responding party. Through a quantitative analysis covering 599 instances of party responsiveness across 172 elections in 30 countries, I find that the extent of vote loss to individual party families is not a better predictor of future electoral platform than the vote share of those party families. This suggests that responding parties are more focused on the opportunities presented by the success of other parties than the threat that they pose. In order to examine the causal mechanism through which responsiveness operates, I present the results of a survey focusing on the informational environment in which parties make decisions about future electoral platforms. Finally, I use qualitative process-tracing to analyse Fianna Fáil’s response to the 2011 Irish general election, and the Liberal Democrats’ response to the 2015 United Kingdom general election. These cases represent instances of high- and low-responsiveness respectively. I find that responsiveness is linked to the extent of shared knowledge within the party about the reasons for vote loss, and that manifestos can be the product of simultaneous responsiveness to multiple stimuli.
APPROVED